The Alexandrian summaries of Galen's on critical days : editions and translations of the two versions of the Jawāmiʻ - Galen. (Islamic Philosophy, Theology and Science. Texts and Studies, 2015)
Galen's impact on Islamic civilization, mainly on medicine but also on physics and philosophy, was enormous. His most important books were mediated through \'summaries\' which not only shortened, but in some cases also revised Galenic teachings. Several versions of these summaries exist, and their appreciation is critical for a proper understanding of the development of medieval science. This book presents the first editions, translations, and studies of the remaining summaries to On Critical Days . In Galenic theory, fevers develop towards a crisis which will determine the fate of a patient. The cycle of crisis is known through observation, but the search for the cause leads Galen and his later interpreters into the fields of astrology, arithmology, and more.